Comparison of domestic tourists expectation and satisfaction on vacation at Bandar Hilir, Malacca, Malaysia - Sapian, Nur Fadhilah (2019)
Bandar Hilir, Malacca is a tourist destination located in Malacca Tengah, Malacca, Malaysia's main as well as international tourist destination. Bandar Hilir, Malacca is rich in heritage tourism assets and well-known historical sources and has its own unique attractions since the colonial era, such as the remnants of building materials. Well, in 2008, Bandar Hilir, Malacca was listed in the area recognized by UNESCO. This makes Bandar Hilir, Malacca remain popular as a destination for world tourism. The main purpose of this study is to determine the satisfaction of domestic tourists based on their expectations and experiences of performance related to accessibility, facilities, attractions, available packages, and facilities while traveling. In addition, this study also aims to determine the socio-demographic of visitors and their travel characteristics to obtain their level of satisfaction in order to prioritize priority travellers based on these 5 factors in order to identify the characteristics and factors that should be given priority during the improvement process. This study involves 300 respondents by distributing solid questionnaires based on the five factors in the form of a Likert scale to answer the expectation and performance of the five factors. In general, the findings of the study were unsatisfactory. The easy to get places to park cars' statement has shown the lowest mean different (μ = -0.30). Furthermore, the studies also show that some issues need to be given priority in repair and maintenance. Ultimately, it can be said that the level of tourism performance faced by tourists meets the expected satisfaction. On average, they didn't put much hope on considerations such as traffic problems. Tourism satisfaction among domestic visitors can be enhanced by creating new facilities, minimizing road use, and adding resource information by creating mobile applications about Bandar Hilir, Malacca, and creating exciting new ones that can attract many potential vacationers such as high-income groups. Overall, the results of this study can be used as regards to advancement in the tourism sector by the governing party.